2004
DOI: 10.1634/stemcells.2004-0061
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cultured Islet‐Derived Progenitor Cells of Human Origin Express Human Albumin in Severe Combined Immunodeficiency Mouse Liver In Vivo

Abstract: Studies in rodents suggest the presence of a hepatopancreatic stem cell in adult pancreas that may give rise to liver cells in vivo. The aim of the present study was to determine the ability of human islet‐derived cells to adopt a hepatic phenotype in vivo. Cultured human islet‐derived progenitor cells that did not express albumin in vitro were stained with the red fluorescent dye PKH26 and injected into the liver of severe combined immunodeficiency mice. After 3 or 12 weeks, red fluorescent cells were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In several animal studies cells were directly injected into the liver tissue [74,63,6] to avoid the requirement of homing. Using this technique, the transplanted cells were observed in the liver tissue, but also in central veins indicating an increased risk of embolization to the lung.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…In several animal studies cells were directly injected into the liver tissue [74,63,6] to avoid the requirement of homing. Using this technique, the transplanted cells were observed in the liver tissue, but also in central veins indicating an increased risk of embolization to the lung.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Ishikawa et al 26 detected human albumin and the HepPar1 antigen in livers of immunodeficient mice, postulating that the engrafted cells from human cord blood "functioned as hepatocytes." However, other scientists 10,13,27,28 (for a review, see Hengstler et al 1 ), including our group, remained skeptical because we observed the expression of some but not all hepatocyte markers that should be expressed by a real human hepatocyte. Because of its high relevance, we decided to study more closely the fate of human stem cells in mouse livers.…”
Section: Discussionmentioning
confidence: 75%
“…2A). All other cell types were handled according to published procedures and have already been extensively characterized in the indicated references: human monocyte-derived NeoHep cells, 11,19 human hepatopancreatic precursor cells, 12,13 and mesenchymal bone marrow stem cells. 14 Cord blood, hepatopancreatic, and mesenchymal stem cells had a fibroblast-like morphology (Supplemental Fig.…”
Section: Characterization Of Human Stem and Precursormentioning
confidence: 99%
“…Tracking and tracing of transplanted cells in mice is required in many Welds of research (Lewin et al 2000;Voura et al 2004;von Mach et al 2004;SchiVer et al 2003;Mohrmann et al 2005;Trost et al 2005;Eger et al 2004). Tracking of individual cells can be achieved by three strategies: (1) expression of marker proteins, such as enhanced green Xuorescent protein (EGFP) or -galactosidase, (2) Xuorescent dyes, exogenously loaded into the cells (Zhang et al 2002) and (3) inorganic nanocrystals or nanoparticles (Koeppel et al 2007;Jaiswal et al 2004;Larson Fig.…”
Section: Discussionmentioning
confidence: 99%